How is an Arabic Lecturer’s Personality Competence as Expected by Students? An Analysis of Students’ Perceptions in Indonesia - Hamidah, Hamidah; Audina, Noor Amalina; Mubarak, Mahfuz Rizqi (Institut Agama Islam Negeri Curup, 2022)
This study aimed to examine students' perceptions of an ideal Arabic lecturer’s personality competence. This study used an exploratory approach with the data collection technique deploying an online questionnaire distributed via a Google Form. After completing the online questionnaire, the researchers also selected three students for individual interviews based on their availability and willingness to participate. This study revealed several important findings: First, Arabic language lecturers must act according to the prevailing norms and feel proud of their profession. Second, an Arabic lecturer must be independent in acting without being influenced by interventions from anyone and have a high work ethic. Third, an Arabic lecturer must be neutral in treating students in the classroom. Fourth, an Arabic lecturer must use polite language when delivering materials and not be arrogant, which could create a tense/scary atmosphere during the learning process. Fifth, an Arabic language lecturer must set an example for students, such as getting used to speaking Arabic in everyday life so that students could imprint the lecturer.